Physical and physiological demands of basketball small-sided games: the influence of defensive and time pressures - Sarah Bredt; Juliana Torres; Laura Diniz; Gibson M. Praça; André Andrade; Juan Morales; Tomaz Rosso; Mauro Chagas (Termedia Publishing House, 2020)
Different small-sided games (SSG) can be used by coaches to induce specific demands on athletes during team sports training. In basketball, defensive and time pressures are common stressors experienced by players during official matches. However, no studies have investigated the effect of changing these variables in SSG during training. We compared the physical and physiological demands of three basketball SSG performed in a half court with two hoops: 3vs3 with man-to-man defence in the half playing area, 3vs3 with man-to-man defence in the full playing area, and 3vs3 with a reduced shot-clock (3vs3HALF, 3vs3FULL, 3vs3RT, respectively). Twelve male U-17 basketball athletes formed four balanced teams. Each team played the three SSG against each other in a random order, totalling 18 SSG. During the SSG, the players wore triaxial accelerometers and heart rate monitors. SSG were filmed to record the players' motor actions. The results showed that 3vs3FULL (p=0.004, d=0.42,small-to-moderate effect) and 3vs3RT (p=0.026, d=0.33,small-to-moderate effect) increased the time spent in higher acceleration zones compared to 3vs3HALF. Both 3vs3FULL and 3vs3RT presented more transition sprints compared to 3vs3HALF. The 3vs3FULL also presented more fakes and the 3vs3RT presented more jumps compared to the 3vs3HALF. Physiological responses presented no differences between the SSG formats. In conclusion, defensive and time pressures increase the physical demand in 3vs3 SSG performed in the half court. The three SSG investigated in this study presented mean heart rate values close to 90% of the maximum heart rate, which suggests that these SSG may be used to increase athletes' aerobic performance.